1994
DOI: 10.1111/j.1399-302x.1994.tb00040.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential pattern of infection and i immune response during experimental oral candidiasis in BALB/c and DBA/2 (H‐2d) mice

Abstract: We used an experimental model of oral candidiasis in the mouse to investigate the impact of the introduction of Candida albicans into a Candida-free system. We report that 2 strains of mice with the same major histocompatibility complex haplotype (H-2d) display different kinetics of primary oral infection after topical application of the same inoculum. The mucosal reactions in both DBA/2 and BALB/c mice involve a similar recruitment of CD4+ and CD8+ T cells and of MAC-1+ cells in mucosal tissue during the infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0
5

Year Published

1999
1999
2010
2010

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 26 publications
2
68
0
5
Order By: Relevance
“…As Samaranayake, Y.H. and L.P. (19) reviewed in 2001, a number of animal models have been described to study oral candidiasis using rabbits (21), rats (9, 18), mice (5,6) and their mutants (7). Compared with them, however, our model can be handled more simply and easily and is not expensive; it can therefore be more useful for screening of antifungals and to investigate the pathogenesis of C. albicans as an oral infection.…”
Section: Discussionmentioning
confidence: 99%
“…As Samaranayake, Y.H. and L.P. (19) reviewed in 2001, a number of animal models have been described to study oral candidiasis using rabbits (21), rats (9, 18), mice (5,6) and their mutants (7). Compared with them, however, our model can be handled more simply and easily and is not expensive; it can therefore be more useful for screening of antifungals and to investigate the pathogenesis of C. albicans as an oral infection.…”
Section: Discussionmentioning
confidence: 99%
“…Inbred mice differ in their susceptibility to systemic infection with the yeast [1e3], and some progress has been made in identifying the genetic basis of these differences [4e6]. In oral candidiasis, the increased tissue susceptibility of CBA/CaH mice relative to BALB/c has been confirmed [7], and DBA/2 mice show slightly different patterns of oral colonisation compared to BALB/c [8,9]. However, the extent to which host responses are related to global virulence properties of different Candida strains has not yet been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…The contrast between the results of Elahi and Farah is of particular interest, as both groups were using the same isolate of the yeast (3630, from the Mycology Reference Laboratory at the Royal North Shore Hospital). After oral infection, DBAJ2 mice showed a bimodal pattern of colonization (Chakir et al, 1994), a feature reproduced by Elahi et al (2000), whereas in the experiments of Farah (Ashman et al, 2003), only a single peak was observed. It seemed probable that the course of oral infection in this mouse strain was influenced by the actual technique used for infection.…”
Section: Role Of the Infectious Challengementioning
confidence: 92%
“…BALB/c and DBA/2 mice are of the same major histocompatibility complex (MHC) type, but BALB/c is C5-suflicient, whereas DBN2 is C5-def,rcient. Although DBN2 mice were somewhat more prone to infection than BALB/c mice (Chakir et al, 1994), oral infection in both strains resulted in an increase in MAC-I* cells and a comparable recruitment of CD4+ and CD8* T lymphocytes into the mucosal tissue. Thus, in contrast to systemic infection, complementderived chemotactic factors appear to have little or no effect on inflammatory processes in the oral mucosa.…”
Section: 21 Studies In Normal Micementioning
confidence: 99%
See 1 more Smart Citation